Vibration-based structural health monitoring using output-only measurements under changing environment - Deraemaeker, A.; Reynders, E.; De Roeck, G.; Kullaa, J. (Mechanical systems and signal processing, 2008)
This paper deals with the problem of damage detection using output-only vibration measurements under changing environmental conditions. Two types of features are extracted from the measurements: eigenproperties of the structure using an automated stochastic subspace identification procedure and peak indicators computed on the Fourier transform of modal filters. The effects of environment are treated using factor analysis and damage is detected using statistical process control with the multivariate Shewhart- T control charts. A numerical example of a bridge subject to environmental changes and damage is presented. The sensitivity of the damage detection procedure to noise on the measurements, environment and damage is studied. An estimation of the computational time needed to extract the different features is given, and a table is provided to summarize the advantages and drawbacks of each of the features studied.